FORMULASI STRATEGI DALAM MENCAPAI KEUNGGULAN BERSAING - Marpaung, Frans Yuda Yonathan; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Café Sawah Pujonkidul Tourism Village is a business unit of BUMDes Sumber Sejahtera. Café Sawah Pujonkidul Tourism Village needs to develop its strategy, especially due to being affected by the current pandemic. The purpose of this research is to produce a strategy that can be used by the company for its business development. The formulation of the appropriate strategy is carried out in three strategic stages, namely the IFE and EFE matrices to determine the strengths, weaknesses, opportunities, and threats. Then the SWOT Matrix to find out where the company is. Then determine the strategy with QSPM. The method used in this research is qualitative, so the form of the results of this study is in the form of writing. Data were collected through interviews and observations. The data was analyzed using management analysis tools. A suitable strategy used by Café Sawah Pujonkidul Tourism Village is market penetration. The alternative market penetration strategy got a score of 6.08, higher than the product development strategy which got a score of 5.49.